Anesthetic Management of Direct Laryngoscopy and Dilatation of Subglottic Stenosis in a Patient with Severe Myasthenia Gravis - Hesham A. Elsharkawy; Ursula Galway (Case Reports in Anesthesiology)
We describe the anesthetic management of a patient with severe myasthenia gravis and tracheal stenosis; the patient was scheduled for direct laryngoscopy and dilatation. The combination of myasthenia gravis and tracheal obstruction presents several difficulties for anesthetic management. The airway is shared; therefore, any complications are also shared by the anesthesiologist and bronchoscopists. The potential for respiratory compromise in patients undergoing the two procedures requires that anesthesiologists be familiar with the underlying disease state, as well as the interaction of anesthetic and nonanesthetic drugs in a case involving myasthenia gravis. We reviewed the literature and report our experience in this case. There is no strong evidence for choosing one approach to general anesthesia over another for bronchoscopy. Careful preoperative planning and experience in airway management and jet ventilation are crucial to prevent an adverse outcome and obtain favorable results.